Budaya Komunikasi Suku Bugis Dan Suku Mandar di SMP Negeri 1 Pasangkayu Provinsi Sulawesi Barat - A. Ilham, Musdalifa (Jurnal Ilmiah Multidisiplin Amsir, 2023)
There are 2 main problems of this research: how is the form of communication culture of Bugis and Mandar tribe in SMP Negeri 1 Pasangkayu?, and how is the speech strategy of Bugis and Mandar tribe in SMP Negeri 1 Pasangkayu? Data were collected by taking notes and listening methods using the tapped technique. Data were analyzed using four stages: data collection, data reduction, data presentation, and conclusion or verification. Furthermore, the result of this research reveals 9 communication forms they are: 1) command form, 2) suggest form, 3) complain form, 4) invite form, 5) ask form, 6) congratulate form, 7) apologize form, 8) joke form, and 9) promise form. Meanwhile, there are 8 direct speech strategies 1) direct command strategy, 2) direct suggest strategy, 3) direct complain strategy, 4) direct invite strategy, 5) direct ask strategy, 6) direct congratulate strategy, 7) direct apologize strategy, and 8) direct promise strategy. There are also 6 undirect speech strategies: 1) indirect command strategy, 2) indirect suggest strategy, 3) indirect complain strategy, 4) indirect invite strategy, 5) indirect ask strategy, 6) indirect apologize strategy.